Evaluation of the Role of Magnetic Resonance Spectroscopy in Diagnosing Alzheimer’s Disease at a Tertiary Care Hospital - Dr. G. Rakesh, Dr. G. Murugan, Dr. Sreepad Yellu, Dr. Ranjit prasad, Dr. Neil Nunes (South Eastern European Journal of Public Health, 2025)
Neurodegenerative disorders encompass a wide range of neurological diseases, often of unknown origin, characterized by genetic predisposition and affecting various neurofunctional systems. These disorders frequently lead to memory disturbances and cognitive impairment, with their prevalence increasing as the population ages. Early detection and accurate classification based on underlying causes are essential for effective management. Magnetic Resonance Imaging (MRI) has become a cornerstone in diagnosing neurodegenerative diseases due to its high tissue contrast, while Magnetic Resonance Spectroscopy (MRS) has emerged as a valuable tool for assessing brain metabolism. MRS provides insights into the biochemical processes occurring in the brain, quantifying metabolites such as N-acetylaspartate (NAA), creatine (Cr), choline (Cho), and myo-inositol (MI), as well as glutamate, glutathione, and gamma-aminobutyric acid (GABA). The aim of this study is to explore the application of 1H-MRS in detecting metabolic changes in individuals with dementia and MCI, comparing them to healthy controls, and distinguishing between various neurodegenerative conditions. By providing a comprehensive view of metabolic alterations, MRS holds promise in advancing the early diagnosis, monitoring, and treatment strategies for neurodegenerative diseases Objectives: To evaluate metabolic irregularities in individuals presenting with dementia and neuro cognitive impairment using MRS and to evaluate utility of MRS in detecting prodromal signs of Alzheimers disease. Methods: A total of fourty cases were included. All patients aged above 18 years with known cases of alzheimers disease andage matched normal patients. MRI Procedure: Based on inclusion criteria with informed consent MRI brain along with MR spectroscopy is done. MRI Analysis: MRI brain is used to assess the brain atrophy and diagnose the alzheimers disease. MR spectroscopy is used to assess the metabolic ratios in hippocampus. ROC analysis is done to derive the cutoff of metabolic ratios for early detection of alzheimers disease. Results: among 40 patients, 26 males and 16 female subjects were enrolled in this study. MRS showed that naa/cr ratio is significantly reduced (p value <0.001, sensitivity 55%, specificity 80%). ROC analysis revealed estimated cutoff values of naa/cr is <1.51 and we propose this cutoff for early detection of alzheimers disease. Conclusions: Magnetic Resonance Spectroscopy (MRS) can serve as a valuable screening tool in the neuroimaging of neurodegenerative diseases and may also function as an adjunctive marker for detecting preclinical Alzheimer's disease in clinical practice.